Thermal insulation coating as well as preparation method and application thereof

By using thermal insulation coatings prepared by power plant fly ash and specific additives, the cost problem in the prior art is solved, and a low-cost thermal insulation coating is realized, with good adhesion and thermal insulation properties, and is suitable for the inside of the metal furnace shell of a high-temperature furnace.

CN119639261APending Publication Date: 2025-03-18SHOUGANG GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411817169.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing thermal insulation coatings are costly and it is difficult to achieve comprehensive performance with good adhesion and strong thermal insulation at low cost.

Method used

Power plant fly ash is used as the main base material, combined with silicon powder, alumina powder, expansion agent, hardener and plasticizer, and anhydrous sodium silicate is used as the main bonding agent. By optimizing the ratio of the base material and the bonding agent, thermal insulation coatings with good adhesion and insulation properties are prepared.

Benefits of technology

It realizes low-cost thermal insulation coatings, with good adhesion, insulation and construction performance, and is suitable for the inside of the metal furnace shell of various high-temperature furnaces, significantly reducing costs and improving energy utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639261A_ABST
    Figure CN119639261A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal insulation coating and a preparation method and application thereof, and belongs to the technical field of thermal insulation coatings. The coating comprises a base material and an adhesive, the base material comprises the following components in parts by mass: 70-85 parts of power plant fly ash, 10-15 parts of silica powder, 5-10 parts of alumina micro powder, 1-5 parts of an expanding agent, 1-5 parts of a hardening agent and 1-5 parts of a plasticizer; the adhesive comprises anhydrous sodium silicate, an adhesive aid and a water reducing agent. By optimizing the ratio of the base material to the adhesive, the heat-preservation and heat-insulation coating obtained at a low cost not only has a good heat-preservation and heat-insulation effect, is suitable for the inner sides of metal furnace shells of various high-temperature furnaces, but also has good viscoplasticity and construction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal insulation coatings, and in particular to a thermal insulation coating and a preparation method and application thereof. Background Art

[0002] With the continuous development of modern industry, energy consumption is increasing day by day. Saving and reducing energy consumption and improving energy utilization have become the direction of today's society. Energy conservation and emission reduction are more valued in the fields of metallurgy, petroleum and chemical industry. Industrial kilns in industrial production are the main energy-consuming equipment, with huge energy consumption every year. During the thermal processing process, industrial kilns consume huge energy, have high heat loss and low thermal efficiency, and are in urgent need of high-quality thermal insulation and refractory materials.

[0003] Usually, the lining of a high-temperature furnace is composed of several layers of refractory materials of different materials. For example, the torpedo tank for transporting molten iron is composed of refractory bricks, refractory castables, refractory fiberboard and steel shell from inside to outside. Practice has proved that applying a layer of thermal insulation coating on the inner wall of the steel shell can reduce the temperature of the steel shell, thereby reducing the temperature drop during the transportation of molten iron. There are three basic requirements for this type of coating: ① Strong adhesion and certain strength. That is, the coating itself is firmly bonded to the metal, and the thermal expansion coefficient is close to that of the metal substrate under the condition of ≤500℃; the coating is not easily scratched off after drying on the metal surface. ② Strong thermal insulation. That is, the thermal conductivity of the coating itself is low and can effectively insulate; ③ Low cost. If the raw material of the thermal insulation coating is made of certain "nano" materials with higher costs, even if it has a thermal insulation effect, it cannot be widely promoted and used due to cost considerations. Summary of the invention

[0004] The present application provides a thermal insulation coating and a preparation method and application thereof to solve the following technical problem: how to achieve the thermal insulation coating having the comprehensive properties of good adhesion and strong thermal insulation at a low cost.

[0005] In the first aspect, the present application provides a thermal insulation coating, which includes: a base material and an adhesive; the base material includes, by mass: 70 to 85 parts of fly ash from a power plant, 10 to 15 parts of silicon micropowder, 5 to 10 parts of alumina micropowder, 1 to 5 parts of an expansion agent, 1 to 5 parts of a hardener, and 1 to 5 parts of a plasticizer; the adhesive includes anhydrous sodium silicate, an adhesive aid, and a water reducer.

[0006] Optionally, the thermal insulation coating satisfies at least one of the following properties: compressive strength at room temperature ≥ 15 MPa, thermal conductivity ≤ 0.23 W / (m·K), and consistency of 130 mm to 160 mm.

[0007] Optionally, the bulk density of the fly ash from the power plant is 0.6 g / cm 3 ~0.9g / cm 3, the particle size of the fly ash from the power plant is ≤0.2mm.

[0008] Optionally, the expansion agent is at least one of bentonite and expanded vermiculite, and the particle size of the expansion agent is ≤200 mesh.

[0009] Optionally, the hardener is at least one of sodium fluorosilicate and aluminum phosphate, and the particle size of the hardener is ≤200 mesh.

[0010] Optionally, the plasticizer is at least one of Guangxi clay and sericite, and the particle size of the plasticizer is ≤200 mesh.

[0011] Optionally, the Baume degree of the anhydrous sodium silicate is ≥56°.

[0012] Optionally, the anhydrous sodium silicate contains SiO2 and Na2O, wherein the mass of the SiO2 is 29.5% to 32.5% of the mass of the anhydrous sodium silicate, and the mass of the Na2O is 13% to 14.5% of the mass of the anhydrous sodium silicate.

[0013] Optionally, the bonding aid is at least one of carboxymethyl cellulose and polyacrylate.

[0014] Optionally, the water reducing agent is at least one of sodium hexametaphosphate and sodium tripolyphosphate.

[0015] Optionally, the mass of the anhydrous sodium silicate is 10% to 25% of the total mass of the base material, the mass of the bonding aid is 0.5% to 2% of the total mass of the base material, and the mass of the water reducer is 0.5% to 2% of the total mass of the base material.

[0016] In a second aspect, the present application provides a method for preparing the thermal insulation coating described in the first aspect, the method comprising:

[0017] Mixing the base materials according to the mass parts to obtain a mixture;

[0018] Dissolving the anhydrous sodium silicate, the bonding aid and the water reducing agent in water to obtain an aqueous solution;

[0019] The mixed material and the aqueous solution are mixed to obtain a thermal insulation coating.

[0020] Optionally, the mass of water in the aqueous solution is 50% to 70% of the mass of the base material.

[0021] In a third aspect, the present application provides an application of the thermal insulation coating described in the first aspect, wherein the thermal insulation coating is used for the inner side of the metal furnace shell of various high-temperature furnaces.

[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0023] The present application provides a thermal insulation coating, the coating comprising: a base material and an adhesive; in parts by mass, the base material comprises: 70 to 85 parts of fly ash from a power plant, 10 to 15 parts of silicon micropowder, 5 to 10 parts of alumina micropowder, 1 to 5 parts of an expander, 1 to 5 parts of a hardener, and 1 to 5 parts of a plasticizer; the adhesive comprises anhydrous sodium silicate, an adhesive aid, and a water reducer. By using fly ash as the main base material and combining a specific mass fraction of silicon micropowder and aluminum micropowder, on the one hand, the coating has higher strength and lower thermal conductivity, and on the other hand, using fly ash, an industrial waste, as a base material helps to save energy, reduce emissions, and reduce costs. The use of expanders and adhesives gives the coating a thermal expansion coefficient and adhesion close to that of metals, so that the coating can be applied to metal surfaces. Adding a plasticizer can give the coating good construction performance. Anhydrous sodium silicate is used as the main adhesive, and carboxymethyl cellulose and / or polyacrylate are used as adhesive aids to ensure that the coating has strong adhesion to the metal surface before and after hardening and is not easy to fall off. In summary, the thermal insulation coating provided in the embodiment of the present application optimizes the ratio of the base material and the adhesive to achieve a low-cost thermal insulation coating that not only has good thermal insulation effects, but is also suitable for the inner side of the metal furnace shell of various high-temperature furnaces, and has good viscosity, plasticity and construction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0026] Figure 1 A schematic flow chart of a method for preparing a thermal insulation coating provided in an embodiment of the present application. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0029] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the weight ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.

[0031] In the first aspect, the present application provides a thermal insulation coating, which includes: a base material and an adhesive; the base material includes, by mass: 70 to 85 parts of fly ash from a power plant, 10 to 15 parts of silicon micropowder, 5 to 10 parts of alumina micropowder, 1 to 5 parts of an expansion agent, 1 to 5 parts of a hardener, and 1 to 5 parts of a plasticizer; the adhesive includes anhydrous sodium silicate, an adhesive aid, and a water reducer.

[0032] Fly ash is used as the main base material, and its low thermal conductivity and high temperature resistance ensure the overall performance of the coating. In the embodiment of the present application, there is no need to screen the fly ash for floating beads or sinking beads, and direct use can achieve good thermal insulation effect, which significantly reduces the cost. Exemplarily, the mass parts of fly ash from power plants can be 70 parts, 73 parts, 76 parts, 79 parts, 82 parts, 85 parts, etc. Silica powder has a higher specific surface area, which can improve the bonding effect between the particles of the coating material, thereby improving the strength. Exemplarily, the mass parts of silica powder can be 10 parts, 11 parts, 12 parts, 13 parts, 15 parts, 15 parts, etc. The smaller particle size of alumina powder can effectively fill the pores between large particles in different particle gradations, thereby improving the wear resistance and mechanical strength of the sample. Exemplarily, the mass parts of alumina powder can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc. The addition of expansion agent adjusts the expansion of the coating, making it close to the thermal expansion coefficient of metal, and enhancing the adhesion and durability of the coating. Exemplarily, the mass parts of the expansion agent can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc. The use of hardener effectively controls the hardening time of the coating and ensures the construction efficiency. Exemplarily, the mass parts of the hardener can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc. The addition of plasticizer improves the viscosity and plasticity of the coating and the construction performance. Exemplarily, the mass parts of the plasticizer can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc.

[0033] Anhydrous sodium silicate is used as the main solvent, and its excellent bonding properties and corrosion resistance ensure the stable application of the coating on the inner side of the metal shell of the high-temperature furnace. The addition of bonding aids improves the adhesion of the coating at the moment of applying or spraying it to the metal surface, ensuring the smooth progress of the construction process. The compound use of water reducers effectively reduces the amount of water added and improves the strength and construction performance of the coating. In summary, the thermal insulation coating provided in the embodiment of the present application optimizes the ratio of the base material and the adhesive to achieve a thermal insulation coating obtained at a low cost. It not only has good thermal insulation effects, but is also suitable for the inner side of the metal shell of various high-temperature furnaces, and has good viscosity, plasticity and construction performance.

[0034] In some embodiments, the thermal insulation coating satisfies at least one of the following properties: compressive strength at room temperature ≥ 15 MPa, thermal conductivity ≤ 0.23 W / (m·K), and consistency of 130 mm to 160 mm.

[0035] By optimizing the ratio of base material and adhesive, the room temperature compressive strength of the thermal insulation coating is ≥15MPa, ensuring the stability and safety of the coating when applied to the inner side of the metal shell of the high-temperature furnace. For example, the room temperature compressive strength of the thermal insulation coating can be 15MPa, 16MPa, 17MPa, 18MPa, 19MPa, 20MPa, etc. The excellent performance of the thermal conductivity of the thermal insulation coating is ≤0.23W / (m·K), which effectively reduces the heat transfer inside the metal shell of the high-temperature furnace and improves the energy efficiency. Exemplarily, the thermal conductivity of the thermal insulation coating can be 0.15W / (m·K), 0.16W / (m·K), 0.17W / (m·K), 0.18W / (m·K), 0.19W / (m·K), 0.20W / (m·K), 0.21W / (m·K), 0.22W / (m·K), 0.23W / (m·K), etc.

[0036] The consistency is also called fluidity, which refers to the measure of the flow performance of the base material under its own weight and / or external force after adding water or other liquid binders and stirring evenly. The general measurement method is that after adding water or other liquid binders and stirring evenly, the base material is loaded into a truncated cone-shaped mold with a lower diameter of 60mm on the platform, the mold is removed, and the slurry begins to spread. The coating is required to have a certain viscosity, cannot flow, and cannot have excessive thixotropic properties such as shear thinning, but can be sprayed smoothly. The embodiment of the present application accurately controls the mass of water in the aqueous solution (50% to 70% of the mass of the base material) so that the consistency of the coating is 130mm to 160mm, ensuring the construction performance and coating quality of the coating. Exemplarily, the consistency of the coating can be 130mm, 135mm, 140mm, 145mm, 150mm, 155mm, 160mm, etc.

[0037] In the embodiment of the present application, the thermal insulation coating can be used in the lining of a torpedo tank for one tank service, i.e., 800 to 1000 times, and has good durability.

[0038] In some embodiments, the bulk density of the power plant fly ash is 0.6 g / cm 3 ~0.9g / cm 3 , the particle size of the fly ash from the power plant is ≤0.2mm.

[0039] Power plant fly ash refers to the fine fly ash and bottom ash produced by coal-fired power plants during the combustion of coal. It is obtained after being collected by a dust collector. It is an industrial waste. The main components are fine powders such as silicon dioxide, aluminum oxide, and iron oxide. It has the characteristics of low thermal conductivity and high temperature resistance, and can be used to make fillers for coatings. Generally, the use of fly ash requires the use of a hydrocyclone method to screen out some raw materials with porous cavity structures inside the fly ash, which are called floating beads or sinking beads. This screening process will undoubtedly increase the cost of fly ash utilization. In order to reduce the cost of raw materials, the embodiments of the present application use special additives and combined processes so that the fly ash raw materials do not need to be screened, and direct use can also achieve better results. Bulk density refers to the mass per unit volume of powder materials in a natural stacking state, and its size is affected by multiple factors such as particle shape, particle size distribution, pore structure, and stacking method. For power plant fly ash, bulk density has a direct impact on its transportation, storage, processing, and final utilization effect. Fly ash with low bulk density takes up a lot of space and is more expensive during transportation. In the storage process, due to its large porosity, it is easy to absorb water and form lumps, which affects subsequent processing. In terms of utilization, fly ash with low bulk density often requires more additives or treatment measures to achieve the ideal performance requirements. Therefore, in the process of resource utilization of fly ash, it is particularly important to reasonably control its bulk density. In the embodiment of the present application, the bulk density of fly ash from a power plant is 0.6g / cm 3 ~0.9g / cm 3 For example, the bulk density of fly ash from a power plant can be 0.6 g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 The particle size of fly ash from power plants is ≤0.2 mm, which ensures the uniformity and fineness of the coating. For example, the particle size of fly ash from power plants can be 0.04 mm, 0.08 mm, 0.12 mm, 0.16 mm, 0.2 mm, etc.

[0040] In some embodiments, the expansion agent is at least one of bentonite and expanded vermiculite, and the particle size of the expansion agent is ≤200 mesh.

[0041] Expansion agents are used to adjust the expansion of the coating to make it close to the thermal expansion coefficient of the metal. Since thermal insulation needs to be applied on the metal furnace shell, and the thermal expansion coefficient of the inorganic non-metallic material such as coating is usually quite different from that of metal, in order to ensure good adhesion of the coating on the metal substrate, the expansion of the coating must be appropriately increased. Otherwise, the coating will quickly crack and fail due to the large difference in thermal expansion with the metal during use. Bentonite has strong water absorption and can absorb water several times its own weight. After absorbing water, its volume expands. Bentonite also has good adhesion and plasticity, which makes it also used as an adhesive in coatings. After high-temperature roasting, the volume of expanded vermiculite can rapidly expand several to dozens of times, forming a fine air spacer, which makes the expanded vermiculite have good thermal insulation and heat insulation properties. Its bulk density is usually between 80 and 200 kg / m 3 The thermal conductivity is low, about 0.047 ~ 0.081 W / (m·K), which further enhances its applicability as a thermal insulation material.

[0042] In some embodiments, the hardener is at least one of sodium fluorosilicate and aluminum phosphate, and the particle size of the hardener is ≤200 mesh.

[0043] The embodiments of the present application mainly use anhydrous sodium silicate as an adhesive, and sodium fluorosilicate is often used as a coagulant for anhydrous sodium silicate binders in refractory materials. It can promote the rapid solidification of anhydrous sodium silicate binders in refractory materials, thereby improving the hardening speed and performance of the material. Aluminum phosphate is an effective inorganic hardener used for the solidification of alkali metal silicate solutions. Polyaluminum phosphate can slowly hydrolyze with anhydrous sodium silicate solutions to release hydrogen ions, thereby promoting the curing process. Therefore, the combination of these two hardeners can effectively control the hardening time of the coating. In order to make the coating easy to construct, its hardening time must be controlled within a suitable range. If the hardening time is too long, the masonry period of the high-temperature furnace will be delayed; if the hardening time is too short, the material will harden rapidly after batching and cannot be coated or sprayed. According to construction experience, the hardening time of the coating in the embodiments of the present application is about 3h to 6h.

[0044] In some embodiments, the plasticizer is at least one of Guangxi clay and sericite, and the particle size of the plasticizer is ≤200 mesh.

[0045] The thermal insulation coating is semi-mud-like when applied. It is a functional material that is applied to the surface of other linings manually or mechanically. Unlike castables, the coating has high viscosity, cannot flow obviously, and cannot have excessive thixotropic properties such as shear thinning. Therefore, a reasonable particle size grading is used to make the coating reach a certain consistency, and Guangxi soil or sericite is used to increase its viscosity and plasticity, thereby achieving good construction performance. The mass fraction of the plasticizer is controlled to be 1 to 5 parts. Clay minerals such as sericite and Guangxi soil can increase the viscosity of the water in the coating at a water content of 50% to 60% in the coating of the embodiment of the present application to form a solid water film, and can also increase the electrostatic repulsion between the particles of the material to form a stable sol-like state, greatly improving the plasticity and adhesion of the material.

[0046] In some embodiments, the anhydrous sodium silicate has a Baume degree ≥ 56°.

[0047] Baume degrees (°Bé) is a method of expressing the concentration of a solution. The degree obtained by immersing a Baume hydrometer in the measured solution is called Baume degrees. For example, the Baume degrees of anhydrous sodium silicate can be 56°, 57°, 58°, 59°, 60°, etc.

[0048] In some embodiments, the anhydrous sodium silicate contains SiO2 and Na2O, wherein the mass of the SiO2 is 29.5% to 32.5% of the mass of the anhydrous sodium silicate, and the mass of the Na2O is 13% to 14.5% of the mass of the anhydrous sodium silicate.

[0049] Adhesives commonly used in coatings include anhydrous sodium silicate, silica sol, and aluminum dihydrogen phosphate. The embodiment of the present application selects anhydrous sodium silicate as the main solvent based on the working environment of the coating. The shell temperature of a high-temperature furnace is usually ≤350°C, and the coating needs to be applied to the shell. At this temperature, the bonding strength of silica sol is less than that of anhydrous sodium silicate and aluminum dihydrogen phosphate. In addition, since the coating needs to be applied to the metal surface, aluminum dihydrogen phosphate is a strong acid adhesive, which will react to a certain extent with the metal surface, causing the coating to fall off. Anhydrous sodium silicate applied to the metal surface will form alkali metal silicate and SiO2 gel film, which protects the metal from corrosion by external acids, alkalis, etc. Therefore, anhydrous sodium silicate is used as the main solvent of the adhesive of the present invention. In order to maximize the bonding effect of anhydrous sodium silicate, the parameters of anhydrous sodium silicate are limited as follows: the mass of the SiO2 is 29.5% to 32.5% of the mass of the anhydrous sodium silicate, and the mass of the Na2O is 13% to 14.5% of the mass of the anhydrous sodium silicate.

[0050] In some embodiments, the bonding aid is at least one of carboxymethyl cellulose and polyacrylate.

[0051] The mechanism of action of anhydrous sodium silicate as an adhesive is that sodium silicate solution reacts with CO2 in the air to generate silica gel, then gradually dries and hardens. The silica gel generated by this reaction has strong adhesion, can block the pores of the material and form a continuous closed film on the surface. This hardening reaction requires a certain time, and the embodiment of the present application can be controlled within 4h. However, during construction, since the metal furnace shell is usually erected, the coating will slide downward under the influence of its own gravity when it contacts the furnace shell surface, so it is hoped that the coating will form a certain adhesion at the moment of applying or spraying to the metal surface. At this time, only the adhesion of the bonding aid can be relied on, i.e., at least one of carboxymethyl cellulose and polyacrylate, both of which are organic binders, and will undergo processes such as dehydration, degradation and carbonization under high temperature conditions, but at this time, the main solvent anhydrous sodium silicate in the adhesive has played a role, so the adhesion of the coating in the whole construction process can be guaranteed.

[0052] In some embodiments, the water reducing agent is at least one of sodium hexametaphosphate and sodium tripolyphosphate.

[0053] Under the premise of ensuring good construction performance of the coating, the amount of water added should be reduced as much as possible, otherwise the coating will produce pores and defects due to the large amount of water added, affecting the strength. Sodium hexametaphosphate is suitable for aluminum micropowder system, and sodium tripolyphosphate is suitable for silicon micropowder system. In the present invention, the combination of the two can achieve a good water reduction effect.

[0054] In some embodiments, the mass of the anhydrous sodium silicate is 10% to 25% of the total mass of the base material, the mass of the bonding aid is 0.5% to 2% of the total mass of the base material, and the mass of the water reducer is 0.5% to 2% of the total mass of the base material.

[0055] Figure 1 A schematic flow chart of a method for preparing a thermal insulation coating provided in an embodiment of the present application.

[0056] See also Figure 1 In a second aspect, the present application provides a method for preparing the thermal insulation coating described in the first aspect, the method comprising:

[0057] S1. Mixing the base materials according to the mass parts to obtain a mixture;

[0058] S2, dissolving the anhydrous sodium silicate, the bonding aid and the water reducing agent in water to obtain an aqueous solution;

[0059] In some embodiments, the mass of water in the aqueous solution is 50% to 70% of the mass of the base material.

[0060] The amount of water added varies according to the construction method: when the construction method is applied by smearing, the mass of water in the aqueous solution is 50% to 60% of the mass of the base material; when the construction method is applied by spraying, the mass of water in the aqueous solution is 60% to 70% of the mass of the base material.

[0061] S3, mixing the mixed material and the aqueous solution to obtain a thermal insulation coating.

[0062] The product prepared by the method for preparing the thermal insulation coating is the above-mentioned thermal insulation coating. Since the method for preparing the thermal insulation coating adopts part or all of the technical solutions of the thermal insulation coating embodiment, it at least has all the beneficial effects brought by the technical solutions of the thermal insulation coating embodiment, which will not be described one by one here.

[0063] Based on a general inventive concept, the present application provides an application of a thermal insulation coating as described in any one of the above embodiments, wherein the thermal insulation coating is used for the inner side of a metal furnace shell of various high-temperature furnaces.

[0064] In some embodiments, the thermal insulation coating can be applied to the inner side of the metal furnace shell of various high-temperature furnaces by coating, or can be applied to the inner side of the metal furnace shell of various high-temperature furnaces by spraying.

[0065] The present application is further described below in conjunction with specific embodiments. The experimental methods in the following embodiments that do not specify specific conditions are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0066] Example 1

[0067] A thermal insulation coating, wherein the base material comprises, by weight:

[0068] 80 parts of power plant fly ash, 10 parts of silicon micropowder, 5 parts of alumina micropowder, 2 parts of bentonite, 2 parts of sodium fluorosilicate and aluminum phosphate, and 1 part of Guangxi soil.

[0069] Take 20% of the weight of the above-mentioned base material anhydrous sodium silicate, 1% of carboxymethyl cellulose and 0.5% of sodium hexametaphosphate + sodium tripolyphosphate, put them into 50% of the weight of the base material water, stir them thoroughly and dissolve them into an aqueous solution.

[0070] After dry stirring the base powder for 3 minutes, slowly add the aqueous solution and wet stir for 3 minutes to form a slurry. At this time, the consistency of the slurry is 140mm, that is, the slurry is applied to the surface of the metal furnace shell by hand. The application time is ≤3h, and the coating thickness formed after the coating hardens is 3mm. The compressive strength at room temperature is 20MPa, and the thermal conductivity is 0.2W / (m·K). Apply to the inner side of the torpedo tank furnace shell, and the furnace shell temperature will drop by 35℃.

[0071] Example 2

[0072] A thermal insulation coating, wherein the base material comprises, by weight:

[0073] 82 parts of power plant fly ash, 8 parts of silica powder, 5 parts of alumina powder, 2 parts of expanded vermiculite, 2 parts of sodium fluorosilicate + aluminum phosphate, and 1 part of sericite.

[0074] Take 20% of the weight of the above-mentioned base material anhydrous sodium silicate, 1% of carboxymethyl cellulose + polyacrylate and 0.5% of sodium hexametaphosphate + sodium tripolyphosphate, put them into 65% of the weight of the base material water, stir them thoroughly and dissolve them into an aqueous solution.

[0075] After dry stirring the base powder for 3 minutes, slowly add the aqueous solution and wet stir for 3 minutes to form a slurry. At this time, the consistency of the slurry is 150mm, that is, the slurry is sprayed on the surface of the metal furnace shell by mechanical spraying. The spraying time is ≤4h, and the coating thickness formed after the coating hardens is 2.5mm. The compressive strength at room temperature is 15MPa, and the thermal conductivity is 0.18W / (m·K). Apply to the inner side of the torpedo tank furnace shell, and the furnace shell temperature will drop by 40℃.

[0076] Example 3

[0077] A thermal insulation coating, wherein the base material comprises, by weight:

[0078] 75 parts of power plant fly ash, 12 parts of silica powder, 6 parts of alumina powder, 4 parts of bentonite + expanded vermiculite, 2 parts of sodium fluorosilicate + aluminum phosphate, and 1 part of Guangxi soil.

[0079] Take 22% of the weight of the above-mentioned base material anhydrous sodium silicate, 1% of carboxymethyl cellulose and 0.5% of sodium hexametaphosphate + sodium tripolyphosphate, put them into 65% of the weight of the base material water, stir them thoroughly and dissolve them into an aqueous solution.

[0080] After dry stirring the base powder for 3 minutes, slowly add the aqueous solution and wet stir for 3 minutes to form a slurry. At this time, the consistency of the slurry is 155mm, that is, the slurry is sprayed on the surface of the metal furnace shell by mechanical spraying. The spraying time is ≤4h, and the coating thickness formed after the coating hardens is 3mm. The compressive strength at room temperature is 18MPa, and the thermal conductivity is 0.15W / (m·K). Apply to the inner side of the torpedo tank furnace shell, and the furnace shell temperature will drop by 50℃.

[0081] It can be seen from Examples 1 to 3 that the components and mass fractions of the base material and adhesive of the examples are within the required range of the present invention. The room temperature compressive strength of the obtained thermal insulation coating is ≥15MPa, the thermal conductivity is ≤0.23W / (m·K), and the consistency is 130mm~160mm. It has good adhesion, extremely low cost and strong thermal insulation, and can play a role in thermal insulation of high-temperature containers.

[0082] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0083] (1) The thermal insulation coatings commonly used in the market are mainly made of glass microspheres, ceramic microspheres or aluminum silicate fibers as the main raw materials, with some nanomaterials added. Although the thermal conductivity is low, the cost is relatively high. According to calculations, the cost of the coating provided by the embodiment of the present invention is only about 10% of the mainstream thermal insulation coatings, which has a great cost advantage.

[0084] (2) At present, fly ash is usually used as a substitute for some raw materials in thermal insulation materials. The amount of fly ash added is usually no more than 30% of the total amount of raw materials, and the fly ash must be screened, which has certain limitations. The present invention uses fly ash as the main base material, the amount of which reaches 80%, and it does not need to be screened and can be directly used, which has great promotion value.

[0085] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.

Claims

1. A thermal insulation coating, comprising: Base materials and adhesives; In parts by mass, the base material includes: 70 to 85 parts of fly ash from a power plant, 10 to 15 parts of silicon micropowder, 5 to 10 parts of alumina micropowder, 1 to 5 parts of an expander, 1 to 5 parts of a hardener, and 1 to 5 parts of a plasticizer; The adhesive comprises anhydrous sodium silicate, an adhesive auxiliary agent and a water reducing agent.

2. The thermal insulation coating according to claim 1, characterized in that: The thermal insulation coating meets at least one of the following properties: room temperature compressive strength ≥ 15 MPa, thermal conductivity ≤ 0.23 W / (m·K), and consistency of 130 mm to 160 mm.

3. The thermal insulation coating according to claim 1, characterized in that: The bulk density of the fly ash from the power plant is 0.6 g / cm 3 ~0.9g / cm 3 , the particle size of the fly ash from the power plant is ≤0.2mm.

4. The thermal insulation coating according to claim 1, characterized in that: The swelling agent is at least one of bentonite and expanded vermiculite, and the particle size of the swelling agent is ≤200 mesh; and / or, The hardener is at least one of sodium fluorosilicate and aluminum phosphate, and the particle size of the hardener is ≤ 200 mesh; and / or, The plasticizer is at least one of Guangxi clay and sericite, and the particle size of the plasticizer is ≤200 meshes.

5. The thermal insulation coating according to claim 1, characterized in that: The Baume degree of the anhydrous sodium silicate is ≥56°; and / or The anhydrous sodium silicate contains SiO2 and Na2O, wherein the mass of the SiO2 is 29.5% to 32.5% of the mass of the anhydrous sodium silicate, and the mass of the Na2O is 13% to 14.5% of the mass of the anhydrous sodium silicate.

6. The thermal insulation coating according to claim 1, characterized in that: The adhesive aid is at least one of carboxymethyl cellulose and polyacrylate; and / or, The water reducing agent is at least one of sodium hexametaphosphate and sodium tripolyphosphate.

7. The thermal insulation coating according to claim 1 or 5, characterized in that: The mass of the anhydrous sodium silicate is 10% to 25% of the total mass of the base material, the mass of the bonding aid is 0.5% to 2% of the total mass of the base material, and the mass of the water reducer is 0.5% to 2% of the total mass of the base material.

8. A method for preparing a thermal insulation coating according to any one of claims 1 to 7, characterized in that: The method comprises: Mixing the base materials according to the mass parts to obtain a mixture; Dissolving the anhydrous sodium silicate, the bonding aid and the water reducing agent in water to obtain an aqueous solution; The mixed material and the aqueous solution are mixed to obtain a thermal insulation coating.

9. The method according to claim 8, characterized in that The mass of water in the aqueous solution is 50% to 70% of the mass of the base material.

10. Use of the thermal insulation coating according to any one of claims 1 to 7, wherein the thermal insulation coating is used for the inner side of the metal furnace shell of various high-temperature furnaces.